Canine medial retropharyngeal lymph node measurements on T2 spin-echo sequences at 3T - DuPont, Emily B.; Boudreau, Elizabeth (Frontiers in Veterinary Science, 2024)
IntroductionThe objective of this study is to estimate reference values for medial retropharyngeal lymph nodes (MRLNs) measured in high-field (3T) MRI studies of the canine head/brain using transverse T2 spin-echo images and to determine if dogs with structural brain disease exhibit medial retropharyngeal lymph nodes that are larger than expected from estimated reference values.MethodsThe study population comprises 142 MRLNs from 71 dogs with no evidence of structural brain disease and normal CSF evaluation and 116 MRLNs from 58 dogs with structural brain disease confirmed by histopathology as of infectious or neoplastic origin, or to represent meningoencephalitis of unknown etiology.ResultsBased on this sample, MRLNs are expected to measure 2.9–12.4 mm in maximum short-axis transverse diameter. Interobserver measurement differences are ~1 mm in 95% of the sampled subjects. Lymph node size is correlated with body weight (R = 0.47–0.52) and age (R = −0.39 – −0.47).DiscussionNo difference was found between the lymph node size of dogs with structural brain disease of any type, or overall, compared to that of dogs without structural brain disease.